1998
DOI: 10.1073/pnas.95.20.11679
|View full text |Cite
|
Sign up to set email alerts
|

Conformational gating of the electron transfer reaction Q A Q B → Q A Q B in bacterial reaction centers of Rhodobacter sphaeroides determined by a driving force assay

Abstract: The mechanism of the electron transfer reaction, Q A ؊ ⅐ Q B 3 Q A Q B ؊ ⅐ , was studied in isolated reaction centers from the photosynthetic bacterium Rhodobacter sphaeroides by replacing the native Q 10 in the Q A binding site with quinones having different redox potentials. These substitutions are expected to change the intrinsic electron transfer rate by changing the redox free energy (i.e., driving force) for electron transfer without affecting other events that may be associated with the electron transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
235
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(250 citation statements)
references
References 47 publications
11
235
0
1
Order By: Relevance
“…The first electron transfer step, which is the focus of this work, occurs with an observed rate constant k AB (1) , which is in the time range 10 4 -10 5 s −1 (9,21,22). The kinetic decay is best described by the sum of several exponential components indicating that the reaction involves more than one step (22,23).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…The first electron transfer step, which is the focus of this work, occurs with an observed rate constant k AB (1) , which is in the time range 10 4 -10 5 s −1 (9,21,22). The kinetic decay is best described by the sum of several exponential components indicating that the reaction involves more than one step (22,23).…”
mentioning
confidence: 97%
“…However, this is unlikely given the independence of the rate on the length of the isoprenoid chain of Q B (9,41,42) and the observation of the same rate constant k AB (1) measured in a mutant RC in which Q B was predominantly structurally located in the proximal site (29). Another possible gating mechanism involves a conformational change in the protein that is required to favor the Q A −• Q B → Q A Q B −• reaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The PT rate constant belonging to kinetic phase 1 of WT-bRC was estimated to be 10 5 s Ϫ1 (3). It was suggested that the ET corresponding to kinetic phase 1 is coupled to a ''conformational gating'' step governed by protein dynamics, which constitutes the rate-limiting step for k AB (1) (4). The second ET event corresponding to kinetic phase 2 (Eq.…”
mentioning
confidence: 99%